Peran Wanita Karier Sebagai Ibu Rumah Tangga Dalam Pembinaan Akhlak Anak: (STUDI TERHADAP WANITA KARIER DI IAIN SORONG) - Nuraini, Novita Dwi; Ramli, Muhammad (MISOOL: Jurnal Pendidikan Dasar, 2020)
This study discusses "The Role of Career Women as Housewives in Fostering Children's Morals". The purpose of this study was to determine the role of career women as housewives in fostering children's morals and to find out the problems faced by career women in fostering the morals of their children. The type of research used is a type of qualitative research. The approach used is a qualitative descriptive approach that describes and analyzes the problems raised by the informants. Data collection techniques are based on primary data and secondary data. The main data used include observation (observation) and interviews. Meanwhile, secondary data are data obtained from the documentation. The data analysis in this thesis uses data triangulation. The results of the study indicate that the role of career women in fostering children's morals is to continue to accompany and provide education, especially religious education to their children. Education that is implanted as an effort to foster children's character is faith education, such as the pillars of Islam and the pillars of faith. Then worship education, such as prayer, ablution, and tayammum and reading the Qur'an. And of course, moral education, such as honesty, discipline, likes to help others, has a cheerful face every time you meet other people, likes to say sorry, asks for help and thanks as a form of respect for others, and behaves and speaks well. To support these efforts, several career women send their children to Islamic-based schools and some choose Islamic boarding schools as a place for their children to deepen their religious knowledge. Meanwhile, the problem faced by career women in fostering the morals of their children is the limited time to accompany and provide education to their children